1987
DOI: 10.1159/000118403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pimozide on Positive and Negative Symptoms in Schizophrenic Patients: Are Negative Symptoms State Dependent?

Abstract: In a double-blind, placebo-controlled trial of treatment with the neuroleptic pimozide, negative symptoms improved in schizophrenic patients who showed an antipsychotic response. Furthermore, there was a significant positive correlation between changes in positive and negative symptoms for the group as a whole, including both pimozide responders and nonresponders. In our patient sample, neuroleptic treatment did not exert a differential effect on the positive and negative symptoms of schizophrenia. It is conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
1
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 16 publications
1
3
1
1
Order By: Relevance
“…In agreement with the findings of other recent studies (Breier et al 1987;vanKammen et al 1987;Kay and Singh 1989;Tandon et al 1990;Meltzer, 1990;Serban et ai 1992), these data confirm that both positive and negative symptoms improve significantly with neuroleptic treatment, Similar to the findings of these studies, we observed that positive symptoms improved to a greater extent than negative symptoms, The significant correlation between change in positive and negative symptoms noted in this study is in agreement with our previous study and the findings of vanKammen et al (I 987) and Meltzer (1990), but inconsistent with Breier et al (1987) and Serban et ai, (1992), who did not find such a relationship, I~reicr et al's inability to find this relationship may have been related to their relatively small sample size (19), Serban et al (1992) studied a sample of "negative schizophrenics" and excluded patients with more than moderate positive symptoms; their ability to detect covariance between positive and negative symptoms may have been limited by the restricted range of positive symptoms in their sample, Meltzer (1990) noted covariance of positive and negative symptoms in the course of treatment of schizophrenic patients with typical neureleptics but not with clozapine,…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with the findings of other recent studies (Breier et al 1987;vanKammen et al 1987;Kay and Singh 1989;Tandon et al 1990;Meltzer, 1990;Serban et ai 1992), these data confirm that both positive and negative symptoms improve significantly with neuroleptic treatment, Similar to the findings of these studies, we observed that positive symptoms improved to a greater extent than negative symptoms, The significant correlation between change in positive and negative symptoms noted in this study is in agreement with our previous study and the findings of vanKammen et al (I 987) and Meltzer (1990), but inconsistent with Breier et al (1987) and Serban et ai, (1992), who did not find such a relationship, I~reicr et al's inability to find this relationship may have been related to their relatively small sample size (19), Serban et al (1992) studied a sample of "negative schizophrenics" and excluded patients with more than moderate positive symptoms; their ability to detect covariance between positive and negative symptoms may have been limited by the restricted range of positive symptoms in their sample, Meltzer (1990) noted covariance of positive and negative symptoms in the course of treatment of schizophrenic patients with typical neureleptics but not with clozapine,…”
Section: Discussionsupporting
confidence: 94%
“…Although poor response to neuroleptics has traditionally been considered a characteristic feature of negative schizophrenic symptoms (Crow 1980;Andreasen et aJ 1982), several recent studies have documented significant improvement in negative symptoms in schizophrenic patients treated with neuroleptics (Breier et al 1987;vanKammen et al 1987;Kay and Singh 1989;Tendon et al 1990;Meltzer, 1990, Serban et al 1992. The question of whether neuroleptic-induced improvement in negative symptoms is linked to concomitant improvement in positive symptoms (vanKammen et al 1987;Tendon et al 1990;Meltzer 1990) or occurs independently of such improvement (Breier et al 1987;Serban et al 1992) is unresolved. This issue has obvious pathophysiological and therapeutic relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that when typical neuroleptics are initially effective, they may appear to reduce both the positive and negative symptoms of schizophrenia (21)(22)(23)(24)(25)(26). However, conventional neuroleptics reportedly fail to provide a sustained reduction in primary or deficit negative symptoms for the majority of patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining the acute phase, with a time span of several weeks, raised the possibility of short-term association, but remained inconclusive. Taken together—from no relationship (Breier et al 1987; Serban et al 1992) to strong positive association (van Kammen et al 1987; Tandon et al 1990, 1993)—variable findings have been reported. However, the results of these studies are hard to interpret because of certain design limitations.…”
mentioning
confidence: 97%